Negative emission power plants: Techno-economic analysis of a biomass-based integrated gasification solid oxide fuel cell/gas turbine system for power, heat, and biochar co-production—part 2 - Jaiganesh, N.; Kuo, Po-Chih; Champatan, Vipin; Gopi, Girigan; Kumar, R. Ajith; Aravind, P.V. (Frontiers in Energy Research, 2022)
In our previous work (Part I), we evaluated the thermodynamic models of the biomass-fed integrated gasification solid oxide fuel cell system with a carbon capture and storage (BIGFC/CCS) unit. In this work (Part II), the techno-economic analysis of the proposed negative emission power plants is carried out. Levelized cost of electricity, net present value (NPV), payback period, internal rate of return (IRR), and levelized cost of negative carbon (LCNC) are the key economic parameters evaluated. The results of a series of sensitivity analysis show the impact of gasification agents and stepwise increase in biochar co-production on the performance of the system. The total overnight cost is estimated to be 6197 /kW and 5567 /kW for the air and steam-oxygen gasification BIGFC/CCS systems, respectively. Steam-oxygen gasification is found to be more economically beneficial than air gasification one for all of the cases studied. Economically viable biochar co-production cases are identified to ascertain the influence of capital cost, operating cost, biomass cost, plant capacity factor, and tax. Moreover, the effect of the carbon credit scenario on the economic indicators is also reported. The results show that the most effective economic performance from the steam-oxygen gasification case reported an NPV of 3542 M, an IRR of 24.2%, and a payback period of 3.3 years, with an LCNC of -322.5/t of CO2. Compiling the results from Part I and Part II shows that it is easier to achieve negative emission using the steam-oxygen gasification of a BIGFC/CCS system. These results are expected to be helpful for stakeholders in identifying appealing negative emissions power plant projects for near and long-term future investments.